BAHASA SEBAGAI JEMBATAN BUDAYA: PERAN BAHASA INDONESIA BAGI PENUTUR ASING DALAM MEMPERKENALKAN IDENTITAS INDONESIA - Rahma Hidayati; Arlin Septia Basana Siagian; Icut Aprilla; Safinatul Hasanah Harahap (STKIP Subang, 2026)
Language is one of the most fundamental elements of culture in shaping and transmitting the identity of a nation. This article examines the role of the Indonesian language as a cultural bridge for foreign speakers in the process of recognizing and understanding Indonesian identity amid the increasingly rapid currents of globalization. Using a sociolinguistic and cultural studies approach, this article analyzes how the mastery of Indonesian by foreign speakers does not merely function as a tool of communication, but also as a medium for understanding the values, social norms, local wisdom, and cultural diversity that characterize the Indonesian nation. The findings indicate that foreign speakers who learn Indonesian undergo a profound process of cultural identity negotiation, while simultaneously contributing to the dissemination of Indonesia's image on the international stage. This article also discusses the challenges and opportunities encountered in learning Indonesian as a foreign language, as well as its implications for cultural diplomacy and the strengthening of Indonesia's position in global forums.